Clinical evaluation of PF614, a novel TAAP prodrug of oxycodone, versus OxyContin in a multi‐ascending dose study with a bioequivalence arm in healthy volunteers - D. Lynn Kirkpatrick; Cari Evans; Linda A. Pestano; Jeffrey Millard; Matthew Johnston; Emily Mick; William K. Schmidt (Wiley, 2024)
Abstract PF614, a trypsin‐activated abuse protection oxycodone prodrug designed to reduce recreational drug abuse, was compared to OxyContin for safety and pharmacokinetics (PKs) of plasma oxycodone following oral administration. This study was a two‐part design including a multi‐ascending dose (part A) and a bioequivalence (BE) study (part B) in healthy volunteers. In part A, 24 subjects were randomized 3:1 to receive PF614 (50, 100, or 200 mg, n = 6/cohort) or OxyContin (20, 40, or 80 mg; n = 2/cohort) in ascending cohorts, delivered every 12 h for a total of nine doses. In part B, 60 subjects randomized in a four‐way crossover to evaluate BE, received PF614 100 mg and OxyContin 40 mg in fasted and fed (high‐fat diet) states. All subjects were naltrexone blocked prior to first study drug administration to protect against opioid‐related adverse effects; repeat doses were provided on days 1-5. In part A, PF614 was well‐tolerated following twice daily doses of up to 200 mg for 5 days. Plasma oxycodone maximal plasma concentration and area under the concentration time curve increased linearly with increasing doses. Part B showed that plasma oxycodone BE was achieved following 100 mg PF614 or 40 mg OxyContin under both fasted and fed conditions. Additionally, PF614 provided similar oxycodone exposures following both fasted and fed states. This study confirms findings from our single‐ascending dose study, showing that PF614 100 mg releases oxycodone with a PK profile comparable to 40 mg OxyContin under both fasted and fed conditions and with a similar safety profile under naltrexone‐blocked conditions.